2014
DOI: 10.1371/journal.pone.0086399
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Sequencing, Assembly, and Analysis of the Root Transcriptome of Persea americana (Mill.) in Response to Phytophthora cinnamomi and Flooding

Abstract: Avocado is a diploid angiosperm containing 24 chromosomes with a genome estimated to be around 920 Mb. It is an important fruit crop worldwide but is susceptible to a root rot caused by the ubiquitous oomycete Phytophthora cinnamomi. Phytophthora root rot (PRR) causes damage to the feeder roots of trees, causing necrosis. This leads to branch-dieback and eventual tree death, resulting in severe losses in production. Control strategies are limited and at present an integrated approach involving the use of phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 79 publications
(93 reference statements)
1
39
0
1
Order By: Relevance
“…In Europe, P. plurivora , P. cambivora and P. cactorum caused a decline of beech trees, with collar cankers and fine‐root loss (Jung, ; Jung et al., ). In France, Spain and Portugal, P. cinnamomi has a broad host range, and it is causing a serious decline of Quercus suber and Q. ilex in those regions (Reeksting, Coetzer, Mahomed, Engelbrecht, & van den Berg, ). Phytophthora cinnamomi may also kill beech, black locust, cedar, Eucalyptus and camellia (Balci & Halmschlager, ,; Hansen & Delatour, ; Ho, Lu, & Gong, ; Shearer & Dillon, ; Shen, Shi, Hong, & Liu, ; Zhou et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, P. plurivora , P. cambivora and P. cactorum caused a decline of beech trees, with collar cankers and fine‐root loss (Jung, ; Jung et al., ). In France, Spain and Portugal, P. cinnamomi has a broad host range, and it is causing a serious decline of Quercus suber and Q. ilex in those regions (Reeksting, Coetzer, Mahomed, Engelbrecht, & van den Berg, ). Phytophthora cinnamomi may also kill beech, black locust, cedar, Eucalyptus and camellia (Balci & Halmschlager, ,; Hansen & Delatour, ; Ho, Lu, & Gong, ; Shearer & Dillon, ; Shen, Shi, Hong, & Liu, ; Zhou et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…El gen de actina (Reeksting et al, 2014) se usó como gen de referencia. Las secuencias de los against the disease.…”
Section: Palabras Clave: Avocado Sunblotch Viroid Persea Americana unclassified
“…The actin gene (Reeksting et al, 2014) was used as a reference gene. Sequences of the primers were taken from the mentioned references.…”
Section: Palabras Clave: Avocado Sunblotch Viroid Persea Americana mentioning
confidence: 99%
“…Recently, Reeksting et al [78] reported the massive sequencing of the root transcriptome of avocado exposed to Phytophthora cinnamomi and flooding using new generation sequencing platforms. The sequencing data generated is available at the NCBI database.…”
Section: Post-genomic Approaches To Understand Avocado Postharvest Rimentioning
confidence: 99%